Prevalence of Cannabis Use Among Medical Students: A Systematic Review and Meta-analysis - Georgios Papazisis; Spyridon Siafis; Ioannis Tsakiridis; Ioannis Koulas; Themistoklis Dagklis; Dimitrios Kouvelas (SAGE Publishing, 2018)
Objective: Cannabis is reported to be the most common illicit substance used among medical students; however, the number of related studies is limited and their results are not systematically reviewed. The aim of our study was to analyze the prevalence of lifetime and current use of cannabis among medical students worldwide. Methods: A systematic review and meta-analysis was performed with adherence to the PRISMA guidelines. The electronic databases PubMed, Scopus, and Cochrane library were searched for studies on the prevalence of cannabis use among medical students. Prevalence of lifetime, past-year, and past-month cannabis use was extracted. Pooled prevalence and relative risk for sex were calculated using the random effects model and subgroup analyses were conducted. Results: A total of 38 observational (cross-sectional and cohort) studies were included (total number of participants 19 932), and most of them were conducted in Europe, Central and Southern America, and the United States. Overall pooled prevalence of lifetime cannabis use was 31.4% (95% confidence interval [CI]: 23.7%-39.6%), past-year use was 17.2% (95% CI: 10.8%-24.6%), and past-month use was 8.8% (95% CI: 5.6%-12.5%). Men displayed higher rates of cannabis use with a pooled relative risk of 1.55 (95% CI: 1.32-1.81). Heterogeneity was high ( I 2  > 75%) and there were differences among continents in all outcomes ( P  < .001). Conclusions: In conclusion, 1 in 3 medical students has used cannabis, whereas 8.8% were current users. Significant differences among continents were observed, but common finding was that male students tend to consume cannabis more often than female students.